Fishery and stock assessment of the blood clamAnadara granosa (Linnaeus) from Kakinada Bay - Rao, G Syda; Somayajulu, K R (Indian Journal of Fisheries, 2011)
Landing and effort data of Anadara granosa (Linnaeus) from Kakinada Baywere collected for the years 1988 to 1991. The landings during 1988 were 802tonnes compared to 1600 tonnes in 1991. The effort in 1988 was estimated at32,458 man-days, which has increased by 1.7 times in 1991. However, catchrates showed a declining trend. There has been some change in the exploitationpattern. Younger size groups (<30 mm) are being exploited more, due to theirhigher price realization. Stock assessment attempted by Jones’ Cohort analysisand Thomson and Bell analysis showed that the current level of exploitationhas already reached MSY level. There is scope to increase the yields by following1990 pattern of exploitation. However, selective exploitation of A. granosa of >30 mm, if continued may lead to declining yields over the years.